Characterization of MADS-box genes in charophycean green algae and its implication for the evolution of MADS-box genes - Tanabe, Yoichi (National Academy of Sciences, 2005)
The MADS-box genes of land plants are extensively diverged to form a superfamily and are important in various aspects of development including the specification of floral organs as homeotic selector genes. The closest relatives of land plants are the freshwater green algae charophyceans. To study the origin and evolution of land plant MADS-box genes, we characterized these genes in three charophycean green algae: the stonewort Chara globularis, the coleochaete Coleochaete scutata, and the desmid Closterium peracerosum–strigosum–littorale complex. Phylogenetic analyses suggested that MADS-box genes diverged extensively in the land plant lineage after the separation of charophyceans from land plants. The stonewort C. globularis mRNA was specifically detected in the oogonium and antheridium together with the egg and spermatozoid during their differentiation. The expression of the C. peracerosum–strigosum–littorale-complex gene increased when vegetative cells began to differentiate into gametangial cells and decreased after fertilization. These expression patterns suggest that the precursors of land plant MADS-box genes originally functioned in haploid reproductive cell differentiation and that the haploid MADS-box genes were recruited into a diploid generation during the evolution of land plants.